Analysis of the Long-Term Impact of Public Debt Policy on Macroeconomic Stability in Indonesia - Buniarto, Edwin Agus; Umasugi, Mohbir; Musyarofah, Atiqatul; Setiawan, Johan; Hartoto, Hartoto (International Journal of Economics (IJEC), 2025)
Public debt policy plays an important role in the Indonesian economy, especially in supporting development financing and maintaining fiscal stability. This study analyzes the long-term impact of public debt on macroeconomic stability, considering indicators such as economic growth, inflation, fiscal balance, exchange rate, and interest rate. This study uses secondary data from Bank Indonesia (BI), Ministry of Finance (MoF), Central Bureau of Statistics (BPS), International Monetary Fund (IMF), and the Indonesian Central Bureau of Statistics (IBPS). Fund (IMF), and the World Bank to identify the relationship between debt policy and national economic stability. The results of the analysis show that although public debt can drive economic growth if used for productive investments such as infrastructure, education, and other strategic sectors, an increase in debt that is not managed properly risks causing fiscal imbalance, inflation, and dependence on foreign financing. The econometric model used in this study shows that Indonesia's economic growth tends to decline when the debt-to-GDP ratio increases significantly. In addition, fluctuations in the rupiah exchange rate and international interest rates also affect the amount of foreign debt payments. This study recommends a more transparent debt management policy that is oriented towards productive investment, diversification of financing sources to reduce exchange rate risk, and fiscal reform to increase state revenues and reduce dependence on debt. With the right strategy, public debt can function as an instrument of sustainable development without sacrificing long-term economic stability.